Relationships between religion, spirituality, and socially responsible engineering. Issue 1 (2nd January 2016) - Bielefeldt, Angela R.; Canney, Nathan E.
ABSTRACT: This research explored the social responsibility (SR) attitudes of engineering students with respect to their self-reported religious beliefs and the religious affiliation of their institution. The study measured SR attitudes using 50 items on a 7-point Likert metric. Over 1900 responses were received in spring 2014 from undergraduate engineering students attending 5 Christian-affiliated and 12 secular universities. On average, students attending Christian-affiliated institutions had more positive SR attitudes than students attending secular institutions. However, an individual's religious beliefs were more important than the institution in predicting SR attitudes. Students who stated that they were very active in an organized religion had more positive attitudes toward SR than students who self-characterized as spiritual, who were in turn more positive than students less active in their religious preference, indifferent, or atheist. College courses were reported to have impacted views of SR by 42–74% of the students attending various institutions; among these students, 32% of the students attending Christian-affiliated institutions indicated that religion-related courses had an impact. The results indicate a need to further explore how religious beliefs impact SR beliefs, toward the goal of more effectively encouraging all engineering students – religious or not – to recognize the importance of socially responsible engineering.